2022
DOI: 10.1007/s00167-022-06995-4
|View full text |Cite
|
Sign up to set email alerts
|

An anatomo-functional implant positioning technique with robotic assistance for primary TKA allows the restoration of the native knee alignment and a natural functional ligament pattern, with a faster recovery at 6 months compared to an adjusted mechanical technique

Abstract: PurposeAn anatomo‐functional implant positioning (AFIP) technique in total knee arthroplasty (TKA) could restore physiological ligament balance (symmetric gap in extension, asymmetric gap in flexion). The purposes were to compare (1) ligament balancing in extension and flexion after TKA in the AFIP group, (2) TKA alignment, implant positioning and patellar tracking between AFIP and adjusted mechanical alignment (aMA) techniques, (3) clinical outcomes between both groups at 12 months. MethodsAll robotic‐assiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 61 publications
(77 reference statements)
2
12
0
1
Order By: Relevance
“…Despite this, similar to the current study, the authors found no difference in KSS scores at one-year follow-up between RO TKA versus CO TKA. [33] Mitchell et al reviewed functional outcomes in 139 consecutive patients undergoing CO TKA versus 148 consecutive patients undergoing RO TKA, and also found comparable UCLA scores and Knee Injury and Osteoarthritis Outcome Scores (KOOS) at one-year follow-up [31]. Similar to the current study, the authors reported excellent clinical results with similar patient-reported outcomes in both treatment groups at one-year follow-up.…”
Section: Discussionsupporting
confidence: 81%
“…Despite this, similar to the current study, the authors found no difference in KSS scores at one-year follow-up between RO TKA versus CO TKA. [33] Mitchell et al reviewed functional outcomes in 139 consecutive patients undergoing CO TKA versus 148 consecutive patients undergoing RO TKA, and also found comparable UCLA scores and Knee Injury and Osteoarthritis Outcome Scores (KOOS) at one-year follow-up [31]. Similar to the current study, the authors reported excellent clinical results with similar patient-reported outcomes in both treatment groups at one-year follow-up.…”
Section: Discussionsupporting
confidence: 81%
“…Consequently, when aiming for neutral alignment by using mechanical alignment approaches in TKA, the native joint orientation is inevitably modiied in many patients [2]. The results indicate the need in individualized alignment paradigms that adjust for variations in individual knee morphology, such as kinematic alignment or personalized alignment approaches [13,22,33,36,37]. BMI is another major factor in TKA failure, and even though we were able to identify a signiicant interaction between knee alignment and a high BMI, the efect was extremely small.…”
Section: Discussionmentioning
confidence: 82%
“…Consequently, when aiming for neutral alignment by using mechanical alignment approaches in TKA, the native joint orientation is inevitably modified in many patients [2]. The results indicate the need in individualized alignment paradigms that adjust for variations in individual knee morphology, such as kinematic alignment or personalized alignment approaches [13, 22, 33, 36, 37].…”
Section: Discussionmentioning
confidence: 99%
“…When combined with a modern medial congruent tibial implant, we believe the Personalized Alignment technique may improve patient satisfaction and clinical outcomes following TKA. A large meta-analysis of 1,112 cases reported greater Western Ontario and McMaster Universities Osteoarthritis (WOMAC) scores, Knee Society Score (KSS), flexion ROM, and walking distance for the KA technique compared to mechanical alignment ( 14 ), and a recent clinical retrospective study reported improved knee and function KSS scores at 6 months with a Personalized Alignment technique compared to non-robotic mechanically aligned TKA ( 26 ). Regarding the MC bearing, a meta-analysis ( 47 ) reported similar WOMAC and KSS, but improved forgotten joint scores with the MC bearing, and clinical studies have shown improved pain, satisfaction, and ROM with the MC compared to posterior stabilized components ( 48 , 49 ).…”
Section: Expected Outcomesmentioning
confidence: 99%
“…Compared to MA, faster recoveries ( 23 ), greater satisfaction rates ( 24 ), and higher outcome scores ( 25 ) have been reported for rKA procedures. On the other hand, personalized TKA requires technologic assistance as standard mechanical instrumentation is likely not accurate enough to achieve patient specific alignment ( 26 ). The ROSA ® Knee System is a semiactive robotic system that controls the placement of cutting jigs and allows the surgeon to use a preferred saw blade for bone resections and dynamic ligament balancing.…”
Section: Introductionmentioning
confidence: 99%